Adolescent victims of sexual abuse and music therapy: A systematic review (Research, Society and Development, 2023)
Background: Sexual violence represents a major public health issue that impacts the future of adolescents. Several studies have examined music therapy as treatment option by suggesting multiples ways on dealing with music experiences. However, not much information in literature is known in professional practice. The current research contributes in understanding use of music as a therapy with adolescent’s victims of sexual abuse. Objective: Identify primary research about music therapy towards adolescents’ victims of sexual abuse to understand context of care, participants’ age, length of therapy, therapist training, clinical goals, methods applied, potentials and issues related to adolescent period of life. Participants and setting: Adolescent, who suffered from sexual abuse in childhood and / or adolescence attending public or private health service. Methods: Qualitative systematic review, seven databases and three specific journals were qualitative systematically searched, as well as been identified primary studies screened against inclusion criteria. Results: Among 492 findings, seven studies between the years 1992 and 2018 were included. Music therapy methodology has been offered in hospitals, private offices, institutions, [of short, medium and long term], by a qualified music therapist; several symptoms were addressed like depression, post-traumatic stress disorder, anxiety with goals to improve social skills; positive affective experiences; emotional self-regulation; autobiographical narrative; expression and communication of ideas and feelings with a variety of methods. Conclusions: Music therapy seems to be an important therapeutic method/tool for young patients who feel comfortable upon music, it facilitates therapeutic bond, helps expression of feelings and is less confrontational therapy.